ANALISIS KATA DASAR DALAM NOVEL LEBÉ KABAYAN KARYA AHMAD BAKRI - Ervina Farhatunnisa; Ratnawati Ratnawati (Jurnal Bastra (Bahasa dan Sastra), 2026)
The purpose of this study is to discuss the analysis of basic words in the novel Lebé Kabayan by Ahmad Bakri, this study focuses on examining the form, meaning and function of basic words. In this study using descriptive qualitative methods. Data acquisition through library study techniques or literature reviews, namely by examining, exploring, recording and identifying reading materials to be studied. To obtain the results of the data in this study is by calculating the frequency and percentage of the data. The results of this study show that there are five forms of basic words, including; 1) one-syllable basic words (220 / 7.6%); 2) two-syllable basic words (2261 / 78.4%); 3) three-syllable basic words (347 / 12%); 4) four-syllable basic words (53 / 1.9%); 5) five-syllable basic words (2 / 0.1%), with a total of 2883 data and a percentage of 100%. The results of the analysis of the meaning of basic words with five parts, including; 1) the meaning of one syllable basic words (220/ 7.6%); 2) the meaning of two syllable basic words (2261/ 78.4%); 3) the meaning of three syllable basic words (347/ 12%); 4) the meaning of four syllable basic words (53/ 1.9%); 5) the meaning of five syllable basic words (2/ 0.1%). The results of the basic word functions found five parts, including; 1) the word item (1365/ 47.3%); 2) the verb (391/ 13.6%); 3) the word sipat (169/ 6%); 4) the word number (34/ 1.1%); 5) the word task (924/ 32%).